IODINE-XENON DATING OF CHONDRULES FROM THE QINGZHEN AND KOTA KOTA ENSTATITE CHONDRITES - Whitby J.A.; Gilmour J.D.; Turner G.; Prinz M.; Ash R.D. (My University, 2002)
Initial 129I/127I values (I-Xe ages) have been obtained for individual mineralogically characterized chondrules and interchondrule matrix from the enstatite chondrites Qingzhen (EH3) and Kota Kota (EH3). In view of the absence of aqueous alteration and the low-peak metamorphic temperatures experienced by these meteorites, we suggest that the I-Xe ages for the chondrules record the event in which they were formed. These ages are within the range recorded for chondrules from ordinary chondrites, demonstrating that chondrules formed during the same time interval in the source regions of both ordinary chondrites and enstatite chondrites. The timing of this chondrule-forming episode or episodes brackets the I-Xe closure age of planetesimal bodies such as the Shallowater aubrite parent body. Although chondrule formation need not have occurred close to planetesimals, the existence of planetesimals at the same time as chondrule formation provides constraints on models of this process. Whichever mechanisms are proposed to form and transport chondrules, they must be compatible with models of the protosolar nebula which predict the formation of differentiated bodies on the same timescale at the same heliocentric distance.